Correlation Between Knowledge About the Provision of Covid-19 Vaccines to The Anxiety Level of Pregnant Women at The Adiluhur Health Center in Mesuji Regency - Veronica, Septika Yani; Agustriyani, Feri; Isnaini, Maulia; Mukhlis, Hamid (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Covid-19 is an infectious disease caused by a virus and is currently still an epidemic. The World Health Organization (WHO) declared Covid-19 a pandemic and became a national emergency status in Indonesia on March 9, 2020. The prevalence of Covid-19 in the world as of January 10, 2022, was 305 million positive cases, with 5.48 million deaths. While vaccine coverage for pregnant women is still low at 30,000 people, most of them refuse to be vaccinated. Vaccination of pregnant women at the Adiluhur Public Health Center in 2021 is 45%. This research objective was to determine the correlation between knowledge about giving the Covid-19 vaccine to the anxiety level of pregnant women at the Adiluhur Public Health Center of Mesuji Regency in 2022.The prevalence of Covid-19 in the world as of January 10, 2022, was 305 million positive cases, with 5.48 million deaths. While vaccine coverage for pregnant women is still low at 30,000 people, most of them refuse to be vaccinated. Vaccination of pregnant women at the Adiluhur Public Health Center in 2021 is 45%. This research objective was to determine the correlation between knowledge about giving the Covid-19 vaccine to the anxiety level of pregnant women at the Adiluhur Public Health Center of Mesuji Regency in 2022.The results showed that the respondents' knowledge was mostly in the good category as many as many as 32 people (57.1%), respondents' anxiety was mostly in the mild category as many as 25 people (44.6%). Statistical results showed that there is a correlation between knowledge and anxiety of pregnant women at the Adiluhur Public Health Center of Mesuji Regency in 2022. The suggestion health workers to cooperate with the Public Health Center in developing vaccination programs for pregnant women and programs that can increase understanding of pregnant women about giving vaccines through related health education vaccination. Abstrack : Covid-19 adalah penyakit menular yang disebabkan oleh virus dan saat ini masih menjadi wabah. World Health Organization (WHO) menetapkan Covid-19 sebagai pandemi dan menjadi status darurat nasional di Indonesia pada 9 Maret 2020. Prevalensi Covid-19 di dunia per tanggal 10 Januari 2022 adalah sebesar 305 juta kasus positif, dengan 5,48 juta kasus meninggal dunia. Sedangkan cakupan vaksin pada ibu hamil masih rendah sebesar 30.000 orang, sebagian besar menyatakan penolakan untuk divaksin. Vaksinasi Ibu hamil di Puskesmas Adiluhur pada tahun 2021 sebesar 45%. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan tentang pemberian vaksin Covid-19 terhadap tingkat kecemasan ibu hamil di Puskesmas Adiluhur Kabupaten Mesuji Tahun 2022. Jenis penelitian ini adalah kuantitatif, menggunakan pendekatan cross sectional. Penelitian di Puskesmas Adiluhur Kabupaten Mesuji pada bulan Januari 2022. Populasi dalam penelitian ini adalah seluruh ibu hamil sebanyak 56 orang, dengan jumlah sampel sebanyak 56 orang. Penelitian mengunakan kuesioner. Analisis data menggunakan analisis Chi-Square. Hasil penelitian mendapatkan pengetahuan responden sebagian besar dalam kategori baik sebanyak 32 orang (57,1%), kecemasan responden sebagian besar dalam kategori cemas ringan sebanyak 25 orang (44,6%). Hasil statistik mendapatkan ada hubungan antara pengetahuan dengan kecemasan ibu hamil di Puskesmas Adiluhur Kabupaten Mesuji Tahun 2022. Bagi tenaga kesehatan, agar dapat bekerjasama dengan Puskesmas dalam membuatkan program vaksinasi untuk ibu hamil dan program yang dapat meningkatkan pemahaman ibu hamil tentang pemberian vaksin melalui penyuluhan kesehatan terkait vaksinasi.